ANALISIS PERTIMBANGAN HAKIM PENGADILAN TINGGI DALAM PUTUSAN NOMOR:37/2019.PT/DPS - NIM. A1012171112, ILHAM RAMADHAN (Jurnal Fatwa Hukum, 2024)
Abstrac  In this scientific work in the form of a thesis, the author gives the title, Analysis of the Judge's Consideration of the High Court in Decision Number: 37/2019.PT / DPS, is the author's effort to analyze the results of the Denpasar High Court Decision which has examined and tried civil cases at the appellate level, and has handed down a decision in the lawsuit case, namely strengthening the district court's decision that rejected all default claims of the Plaintiff against the Defendant.   The author emphasizes the formulation of the problem in this study regarding the subject, "How is the Consideration of High Court Judges in Decision Number: 37/2019.PT/DPS"? The purpose is to analyze the basis for the Judgment of High Court Judges based on Decision Number: 37/2019. PT/DPS and analyze the legal consequences of the High Court judge's decision regarding the payment of fees. So that the author seeks normatively in analyzing Judges' Decisions through the type of normative law research. In addition, it is carried out with a statutory approach (statue approach) in normative legal research related to the legal issue being handled.Based on the legal considerations of the Denpasar High Court Judges in Decision Number: 37 / 2019.PT/ DPS, that because the original Appellants of the Plaintiffs were on the losing side, both in the court of first instance and in the court of appeal, all costs of cases in both levels of court were borne to him in a joint responsibility.As a result of the law of the Court Judge's Decision for the original Comparators, the Plaintiffs were sentenced to the costs of the Plaintiffs' Lawsuit which had been rejected in full in the State District court through Decision Number: 141 / Pdt.G / 2018 / PN. Nga and High Court Decision Number: 37/Pd/2019/PT DPS, which sentenced the Plaintiffs to pay case costs in the District Court in the amount of Rp. 2,587,000,- (two million five hundred and eighty-seven thousand rupiah); and in an appellate court of Rp.150,000,- (one hundred fifty thousand rupiah). Keywords: judge's consideration, default, legal consequences.  Abstrak  Dalam karya ilmiah berbentuk skripsi ini, penulis memberikan judul, Analisis Pertimbangan Hakim Pengadilan Tinggi Dalam Putusan Nomor:37/2019.PT/DPS, merupakan upaya penulis dalam melakukan analisa hasil Putusan Pengadilan Tinggi Denpasar yang telah memeriksa dan mengadili perkara perdata di tingkat banding, dan telah menjatuhkan putusan dalam perkara gugatan tersebut yaitu memperkuat putusan pengadilan negeri yang menolak seluruh gugatan wanprestasi pihak Pengugat terhadap pihak Tergugat.Penulis menitikberatkan rumusan masalah dalam penelitian ini mengenai perihal, "Bagaimana Pertimbangan Hakim Pengadilan Tinggi Dalam Putusan Nomor:37/2019.PT/DPS"? Tujuannya untuk menganalisis dasar Pertimbangan Hakim Pengadilan Tinggi berdasarkan Putusan Nomor: 37/2019. PT/DPS dan menganalisis akibat hukum Putusan hakim Pengadilan Tinggi tersebut terkait pembayaran fee. Sehingga, penulis berupaya secara normatif dalam menganalisis Putusan Hakim melalui jenis penelitian hukum normatif (normative law research). Selain itu, dilakukan dengan pendekatan perundang-undangan (statue approach) dalam penelitian hukum normatif yang berkaitan dengan isu hukum yang sedang ditangani.Berdasarkan pertimbangan hukum Majelis Hakim Pengadilan Tinggi Denpasar dalam Putusan Nomor : 37 / 2019.PT/ DPS, bahwa oleh karena pihak Para Pembanding semula Para Penggugat berada dipihak yang kalah, baik dalam peradilan tingkat pertama maupun dalam peradilan tingkat banding, maka semua biaya perkara dalam kedua tingkat peradilan tersebut dibebankan kepadanya secara tanggung renteng.Akibat hukum Putusan Hakim Pengadilan bagi Para Pembanding semula Para Penggugat dikenai hukuman biaya perkara Gugatan Para Penggugat yang sudah ditolak untuk seluruhnya di pengadilan Negeri Negara melalui Putusan Nomor : 141/Pdt.G/2018/PN.Nga dan Putusan Pengadilan Tinggi Nomor : 37/Pd /2019/PT DPS, yang menghukum Para Penggugat membayar biaya perkara di Pengadilan Negeri berjumlah Rp. 2.587.000,- (dua juta lima ratus delapan puluh tujuh ribu rupiah); dan dalam pengadilan tingkat banding sebesar Rp.150.000,- (seratus lima puluh ribu rupiah).Kata Kunci : Pertimbangan Hakim, Wanprestasi, Akibat Hukum.